The Influence of Digital Marketing on Sales Performance of Batik Nulaba MSMEs in Pekalongan, Central Java - Oseany, Rahma Laila; Kusumaningtyas, Dian; Raharjo, Itot Bian (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
This study analyzes the impact of digital marketing on the sales performance of Batik Nulaba MSMEs in Pekalongan, Central Java. Digital marketing harnesses digital technology and the internet to broaden market reach and enhance consumer engagement. This approach is pivotal in navigating a competitive landscape for micro, small, and medium enterprises (MSMEs). This study employs a quantitative survey method to gather data from Batik Nulaba MSME community participants. The research uses multiple linear regression to evaluate how digital marketing impacts product sales. Results indicate a substantial positive correlation, with social media emerging as the most influential tool. The study emphasizes Batik Nulaba MSMEs' importance in optimizing digital marketing strategies, particularly on social media platforms, to bolster product sales. Recommendations include providing digital marketing training for MSME practitioners, maximizing social media utilization, and collaborating with influencers to expand market penetration. This research advances our understanding of how digital marketing strategies can elevate sales performance among MSMEs, particularly within the batik industry. Batik Nulaba MSMEs can enhance competitiveness and achieve significant sales growth in the digital marketplace by implementing effective digital strategies.